Clinical characteristics, molecular epidemiology and mechanisms of colistin heteroresistance in Enterobacter cloacae complex - Wei, Chunli; Wu, Jiming; Zhang, Jisheng; Liang, Youtao; Yu, Kaixin; Liao, Mingjing; Liang, Xushan; Wang, Jianmin; Long, Wenzhang; Wang, Jin; Chen, Shijian; Yang, Yang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionColistin has emerged as the last resort for treating multidrug-resistant Enterobacter cloacae complex (ECC) infections. The primary purposes of this study were to demonstrate the presence of colistin heteroresistance in ECC and to further investigate their clinical characteristics, molecular epidemiology and mechanisms.MethodsPopulation analysis profiles (PAP) were performed to confirm the heteroresistance phenotype. Average nucleotide identity (ANI) was determined to classify ECC species. Phylogenetic analysis based on core genome single nucleotide polymorphisms (cg-SNPs), multilocus sequence typing (MLST) and core genome MLST (cg-MLST). Risk factors and clinical outcomes of infections were analyzed through a retrospective case-control study. Potential mechanisms of colistin heteroresistance were evaluated using polymerase chain reaction (PCR), efflux pump inhibition assays and reverse transcription quantitative PCR (RT-qPCR).ResultsA high proportion (24.4%) of the non-resistant strains were colistin-heteroresistant isolates. Among the several ECC species, Enterobacter kobei had the largest percentage (29.4%) of colistin-heteroresistant isolates, followed by Enterobacter hormaechei (20.5%) and Enterobacter bugandensis (20.0%). Notably, only one strain (0.8%; 1/132) of Enterobacter hormaechei was fully resistant to colistin. Different ECC species showed varying heteroresistance levels: Enterobacter roggenkampii, Enterobacter kobei, Enterobacter asburiae and Enterobacter bugandensis displayed high heteroresistance levels (MIC ≥ 128 mg/L). 75% of all ST116 and ST56 strains were heteroresistant to colistin. The infection of ST116 and ST56 strains as well as exposure to cephalosporin antibiotics were independent risk factors for colistin-heteroresistant ECC infections. Mechanistic analysis revealed that heteroresistance strongly correlated with the overexpression of arnA, regulated by the PhoPQ two-component system (TCS). Notably, mgrB had minimal impact. AcrAB-TolC efflux pump genes showed unsynchronized expression; High acrB expression was strongly associated with colistin heteroresistance, while acrA and tolC were not.DiscussionColistin heteroresistance showed species-dependent variations in levels and prevalence rates. The colistin-heteroresistant mechanisms were complex, involving coordinated regulation of multiple genes. These results highlighted the need for tailored antimicrobial stewardship. In addition, the development of direct, reliable and rapid clinical methods for detecting heteroresistance is essential for improving infection management and prevention.